2022
DOI: 10.1111/1365-2435.14088
|View full text |Cite
|
Sign up to set email alerts
|

High nitrogen‐fixing rates associated with ground‐covering mosses in a tropical mountain cloud forest will decrease drastically in a future climate

Abstract: 1. Tropical mountain cloud forests (TMCF) harbour a high bryophyte (mosses and liverworts) biomass and diversity. Furthermore, the high air humidity makes these forests well suited for bryophyte-associated nitrogen (N 2 ) fixation by cyanobacteria, providing a potentially important source of N input to the ecosystem. However, few studies have assessed bryophyte-associated N input in these ecosystems, and these have focused on epiphytic bryophytes, whereas abundant ground-covering bryophytes have not been inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…They possess unique properties that differ from all other green land plants: their life cycle is dominated by the haploid gametophyte (rather than the diploid sporophyte as in other land plants), they disperse by wind‐borne spores and/or vegetative propagules, they are mostly poikilohydric (i.e., the water content of bryophyte tissues is largely determined by that of the environment), and they are generally very small in stature (Goffinet & Shaw, 2009). This combination of characteristics has allowed bryophytes to thrive under a wide range of environmental conditions from tropical to polar regions, where they are an essential part of the species diversity and play an important role in ecosystem processes such as moisture retention or biogeochemical cycling (Lindo & Gonzalez, 2010; Turetsky et al, 2012; Ah‐Peng et al, 2017; Permin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…They possess unique properties that differ from all other green land plants: their life cycle is dominated by the haploid gametophyte (rather than the diploid sporophyte as in other land plants), they disperse by wind‐borne spores and/or vegetative propagules, they are mostly poikilohydric (i.e., the water content of bryophyte tissues is largely determined by that of the environment), and they are generally very small in stature (Goffinet & Shaw, 2009). This combination of characteristics has allowed bryophytes to thrive under a wide range of environmental conditions from tropical to polar regions, where they are an essential part of the species diversity and play an important role in ecosystem processes such as moisture retention or biogeochemical cycling (Lindo & Gonzalez, 2010; Turetsky et al, 2012; Ah‐Peng et al, 2017; Permin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For our study, we chose the rate of 30 kg N ha −1 yr −1 since tropical regions are thought to have higher and increasing N deposition rates than boreal and subarctic forests. However, measurements of N deposition from the same study site in Peru recently found N deposition rates of only 4.8 kg N ha −1 yr −1 [ 20 ]. Hence, our additions may have been at the high end of the N addition spectrum, which seems to have ensured the inhibition of N 2 fixation in Dicranum sp.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, mosses and associated cyanobacteria in those forests experience near-optimal climate conditions to sustain BNF, and moisture should not limit BNF in mosses here, in contrast to other ecosystems, such as arctic tundra [ 16 ]. Indeed, a recent study from a tropical cloud forest showed that several moss species host N 2 -fixing cyanobacteria, with relatively high N 2 fixation activity [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implications of this on plant communities and biogeochemical processes remain undetermined. Warming field experiments have been shown to have both direct and indirect negative impacts on bryophytes and BNF in Arctic tundra most likely related to decreases in bryophyte cover, increases in vascular plant cover, and reductions in BNF activity (Permin et al ., 2022). Given the ecological importance of BNF as a source of N, reductions in this N input will have consequences for plant productivity and soil C storage that are currently poorly understood.…”
Section: Bryophyte Contributions To the N Cyclementioning
confidence: 99%